Pengalaman Remaja Bali Yang Melakukan Perilaku Self-Injury - Pratama, Putu Yudi Suwetha; Nugrahaeni Widiasavitri, Putu (Green Publisher Indonesia, 2024)
Adolescents face several changes that cause conflict and emotional stress during adolescence. The conflicts and emotional pressure faced by teenagers cause teenagers to experience distress so that teenagers will have difficulty controlling themselves and carry out actions that are detrimental to themselves. In dealing with stressful conditions, teenagers need to develop behavior by implementing coping strategies. However, not all teenagers are able to develop and choose appropriate coping strategies in dealing with stressful conditions, one of which is engaging in self-injury behavior. Self-injury behavior is the behavior of individuals who deliberately hurt or injure themselves with the aim of reducing the emotional problems they are facing. Self-injury behavior has the impact of feeling satisfied because it feels capable of venting negative emotions, however, another impact of self-injury behavior is addiction, which can lead to attempts to commit suicide. It is important for research to be able to describe how teenagers experience self-injury behavior. This research is a qualitative phenomenological research with semi-structured interviews with three teenagers as resource persons. The data obtained was then analyzed using interpretive phenomenology based on Kahija (2017). The results in this study include 1) motives for self-injury behavior, 2) dynamics of self-injury behavior and, 3) experience of carrying out self-injury behavior.